Optical characterization of chiral three-dimensionally periodic photonic crystals fabricated by temporally periodic physical vapor deposition on two-dimensionally periodic substrates - Ricardo A Fiallo; Mark W Horn; Akhlesh Lakhtakia (Journal of Physics Communications)
We fabricated chiral three-dimensionally (3D) periodic photonic crystals (PPCs) with nanoscale features by: first etching two different two-dimensionally (2D) periodic patterns in fused silica and silicon substrates, and then implementing temporally periodic physical vapor deposition (TP-PVD) whereby a collimated vapor flux was directed towards rotating substrates. The patterned substrates as well as the 3D-PPCs were optically characterized in transmission and reflection in relation to the direction of an incident plane wave and the wavelength in the 500-900 nm range, for linear as well as circular polarization states of the incident plane wave. Before TP-PVD, the patterned substrates exhibited opal-like iridescence, and the optical characterization detected nonspecular transmission and Rayleigh–Wood anomalies, consistently with the mathematical predictions for 2D photonic crystals. Iridescence was maintained after TP-PVD. The 3D-PPCs comprise discrete clumps of nanohelixes growing on the unetched regions. Optical characterization of the 3D-PPCs revealed circular-polarization-discriminatory reflection and transmission, Fabry–Pérot resonances, Dyakonov–Tamm waves, nonspecular transmission, and a high-loss regime, but Rayleigh–Wood anomalies could not be unambiguously identified. We expect applications in diverse scenarios wherein matter and circularly polarized light interact.